Sarjana Teknik Industri Kualitas, Tantangan, dan Prospeknya Dalam Era Perdagangan Bebas - Matthias Aroef (Journal of Regional and City Planning, 1996)
The world is undergoing a very rapid change in almost all aspects of life. So does Indonesia. Being a sub system in this  changing  world,  Indonesia  must  adjust  itself  to  fit  to  the  future  world  condition.  According  to  the  General Agreement on Trade and Tariffs, the General Agreement on Trade in Services, a new World Trade Organization will  be  developed.  Competition  in  this  new  world  trade  will  be  international  in  nature  even  in  the  domestic environment, and is perceived to become more and more competitive. It might develop into a cut throat competition.The Indonesian nation that is still a traditional agrarian society with feudal characteristics is changing towards an Industrial and information society in a short time. This requires a socio -cultural change partly already experienced by the urban population. The slowly changing traditional part of the plural society must be given greater speed, and this paper proposes a corporate approach. At the same time a slower process, but more basic in nature, should be handled by the educational institutions.New values and norms and new ways of doing things must be developed in the new Indonesian individual, such as appreciation  of  value  of  time  ,  to  like  change,  be  more  dynamic,  more  creative  and  innovative;  be  more entrepreneurial,  more  professional,  achievement  oriented,  and  competitive; always strive for better -  qualitatively and quantitatively, for improvement, and for progress.This article considers also the changes that are needed in engineering education. The design of the curricula should incorporate contents that develop the new characteristics in the engineer for the future. They shou ld be world class engineers. Since such change should start as early as possible in the formation of the engineer, the curricula of the primary  and  secondary  education  should  also be redesigned. It becomes a gigantic change process that must be carried out. All parties of the domestic system should take part in it.Since  competition  does  not  occur  in  the  business  world  only,  but  will  happen  also  in  the  professions,  the competitiveness  of  the  individuals  must  also  be  strengthened.  Thus  the  whole  national  system  must  change, including the government, the business, and the individual. The change should be completed as early as in the year 2003, when the Asean Free Trade Area comes into effect, and become stronger by the year 2010 when the gates of the  advanced  countries  are  opened,  and  become  very  strong  by  the year 2020 when the gates of the developing countries should be opened.